Effectof Herbal Extract Supplementations In Feed On Serum And Eggyolk Lipid Profile In Jabalpur Colour Layer Birds (Applied Biological Research, 2014)
The present study was conducted to assess the effects of ginger, cinnamon,  chicory and stevia extract-supplemented feeds on lipid profile in serum  and egg yolk of Jabalpur colour birds. Fifty four Jabalpur colour birds of  32 weeks age were randomly divided into 9 groups of 6 birds each. One  group (control) was fed normal basal feed whereas rest groups were fed on  feeds supplemented with alcoholic extracts of various herbs, separately, at  two levels each [ginger, cinnamon and stevia extract mixed with feed @ 2.5  and 5.0 g kg-1feed and chicory extract @ 1.25 and 2.5 g kg-1feed]. Blood  samples were collected on 0, 14th, 28th, 42nd and 56th day and serum  profile showed a decreasing trend on herbal supplementation as compared  to control. The total lipid was low in birds fed chicory (2.5 g kg-1feed) and  cinnamon (5 g kg-1feed) followed by ginger (5 g kg-1feed) and cinnamon  (2.5 g kg-1feed). The serum cholesterol and triglycerides showed more  decrease in cinnamon (5 g kg-1feed) and chicory (2.5 g kg-1feed) fed birds than other groups. The increase in mean HDL concentration was  significant in birds fed cinnamon (2.5 g kg-1feed), and stevia (5 g kg-1feed)  on 56th day. Low LDL and VLDL were observed in birds fed cinnamon (5  g kg-1feed). The lowest concentration of egg yolk lipid and egg yolk  cholesterol was noticed on 56th day in birds fed cinnamon (5 g kg-1feed),  however least egg yolk triglyceride was low in chicory (2.5 g kg-1feed) and  cinnamon (5 g kg-1feed) fed birds.
Keywords: Chicory; cholesterol; cinnamon; ginger; Jabalpur colour bird; total lipid; triglycerides; stevia